For Spain : Indian evening (leaflet) (1937)
018b-0084-001 FOR SPAIN INDIAN EVENING ARRANGED BY SEHRI SAKLATVALA MIRA DEVI Brilliant Classical Dancer from INDIA ANDRIEVA DANCERS IN NATIONAL DANCES OF SPAIN By courtesy of Madame Andrieva SHANTA GANDHI Indian Folk Dances A. BHATTACHARYA INDIAN ORCHESTRA OF CENTURIES-OLD INSTRUMENTS and BABY BHATTACHARYA Speakers : JOHN STRACHEY ISABEL BROWN INDIRA NEHRU (Daughter of President Nehru) REHEARSAL FOR UNDERSTUDIES (ABOUT MALAGA) A New Play by AUBREY MENON FRIDAY, MAR. 12 at 8 p.m. ADMISSION FREE RESERVED SEATS 2/6 1/0 Doors Open 7.15 OBTAINABLE FROM SPAIN-INDIA COMMITTEE, 165 Strand, W.C.2 and Progressive Bookshops FRIENDS HOUSE (GREAT HALL) EUSTON RD. N.W. Printed by by Marston Printing Co. (T.U.), Nelson Place, Cayton Street, E.C.1. 292/946/18b/84